2020
DOI: 10.1021/acs.energyfuels.0c00644
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical Heat Storage Performance of CaO Pellets Fabricated by Extrusion–Spheronization under Harsh Calcination Conditions

Abstract: To improve the CaO/CaCO 3 thermochemical heat storage capacity and the mechanical property of CaO-based material during the repetitive heat storage cycles, CaO pellets were fabricated by the extrusion−spheronization method. The thermochemical heat storage performance of CaO pellets under pressurized carbonation (3−13 bar) and harsh calcination (950 °C, pure CO 2 ) conditions were studied in a dual fixed-bed reactor. The effects of harsh calcination conditions, carbonation conditions, pellet particle size, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 46 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…There is one paper on this topic. Li et al prepare CaO pellets by extrusion–spheronization under harsh calcination conditions, and the thermochemical heat storage performance of the attained CaO pellets is evaluated in a dual fixed-bed reactor.…”
Section: Calcium Loopingmentioning
confidence: 99%
See 1 more Smart Citation
“…There is one paper on this topic. Li et al prepare CaO pellets by extrusion–spheronization under harsh calcination conditions, and the thermochemical heat storage performance of the attained CaO pellets is evaluated in a dual fixed-bed reactor.…”
Section: Calcium Loopingmentioning
confidence: 99%
“…Wang et al25 evaluate the nitrogen sorption capability of a series of Al 2 O 3 -supported Mn-/Febased nitrogen carriers during chemical looping ammonia synthesis.There is one paper on this topic. Li et al26 prepare CaO pellets by extrusion−spheronization under harsh calcination conditions, and the thermochemical heat storage performance of the attained CaO pellets is evaluated in a dual fixed-bed reactor.This VSI is part of the series of VSIs on Recent Advances in Selected Energy Research Areas, launched by Energy & Fuels in January 2021. Further information on this series of VSIs can be found in a related editorial (10.1021/acs.energyfuels.0c04048) 27.…”
mentioning
confidence: 99%
“…Therefore, combining the incorporation of structure stabilizers and granulation is a promising approach to prepare the desirable CaO-based energy storage materials for the TCES system. Li et al , proved that extrusion–spheronization was an effective granulation method to prepare the CaO-based composite pellets with stable thermal energy storage/release capability. Bai et al also found that the structurally improved, TiO 2 -incorporated CaO-based pellets prepared via extrusion–spheronization exhibited the remarkably enhanced cyclic thermal energy storage/release performance.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, TCES outperforms others considering its higher energy density (0.5–1 kW h/kg), extended storage period (theoretically unlimited), and better stability. , High-temperature TCES has recently attracted increasing attention, since it can be integrated to concentrated solar power (CSP) plants. High-temperature TCES has been considered as a promising alternative to molten salt for highly efficient, stable, and long-term energy storage in a CSP plant. , Efforts have been devoted to designing thermochemical materials such as carbonate systems of CaCO 3 /CaO and PbCO 3 /PbO, , redox systems of BaO 2 /BaO, Co 3 O 4 /CoO, and Mn 2 O 3 /Mn 3 O 4 , and ammonia systems of NH 4 HSO 4 /NH 3 and NH 3 /N 2 for high-temperature TCES applications. , …”
Section: Introductionmentioning
confidence: 99%